DEBCRET2go! - Anak Keska, Gibson Gary Leman; Norizan, Saifulrizan; Awang, Dayangku Ruhayah; Noyem, Josephine Avelind; Rahmat, Mariam (2024)
SDG 4: Quality Education emphasizes transparency and accountability in achieving sustainable development goals. Double-entry accounting is a fundamental accounting principle that enhances transparency by ensuring accuracy and completeness in financial reporting. DEBCRET2go! is an innovative application designed to enhance learning experiences beyond traditional classroom settings. By addressing a broad spectrum of educational needs, including K-12 education, higher education, and professional development, DEBCRET2go! offers several benefits that align with SDG 4: Quality Education. This apps also ensures that financial resources are managed effectively and that educational initiatives are reported accurately, ultimately supporting the successful achievement of sustainable development goals.